INHIBITORY ACTIVITY OF Trichoderma harzianum AGAINST PUTATIVELY PATHOGENIC FUNGUS ON RODENT TUBER (Typhonium flagelliforme) PLANT - Sriherwanto, Catur (Jurnal Bioteknologi & Biosains Indonesia (JBBI), 2022)
Trichoderma spp. are globally considered as the most dominant biofungicide in the market. Reports on Trichoderma spp. efficacy against pathogenic fungi in commercial crops have been numerous, but much less in medicinal plants. This study aimed at testing the potential biofungicidal activity of Trichoderma harzianum in inhibiting the growth of a putatively pathogenic fungus isolated from rodent tuber (Typhonium flagelliforme) plant. The methods consisted of isolation of fungi from the plant’s surface, soil, and polybags. The isolates were then screened for their putative pathogenicity against rodent tuber before being subjected to 16S rRNA molecular identification and in vitro antagonist test using T. harzianum. Result showed that only isolate K4 showed pathogenicity on T. flagelliforme, and was molecularly identified as Lasiodiplodia theobromae, known globally as fungal pathogen attacking various plants. L. theobromae was inhibited by T. harzianum with inhibition index of 23.0 ± 4.3%, which was about twice higher than that of the positive control nystatin 100.000 IU mL (11.1 ± 0.6%). In conclusion, T. harzianum inhibited the growth of L. theobromae in vitro, hence indicating its biofungicidal potential.